The prognostic value of 19S ATPase proteasome subunits in acute myeloid leukemia and other forms of cancer - Tychhon, Boranai; Allen, Jesse C.; Gonzalez, Mayra A.; Olivas, Idaly M.; Solecki, Jonathan P.; Keivan, Mehrshad; Velazquez, Vanessa V.; McCall, Emily B.; Tapia, Desiree N.; Rubio, Andres J.; Jordan, Connor; Elliott, David; et al. (Frontiers in Medicine, 2023)
The ubiquitin-proteasome system (UPS) is an intracellular organelle responsible for targeted protein degradation, which represents a standard therapeutic target for many different human malignancies. Bortezomib, a reversible inhibitor of chymotrypsin-like proteasome activity, was first approved by the FDA in 2003 to treat multiple myeloma and is now used to treat a number of different cancers, including relapsed mantle cell lymphoma, diffuse large B-cell lymphoma, colorectal cancer, and thyroid carcinoma. Despite the success, bortezomib and other proteasome inhibitors are subject to severe side effects, and ultimately, drug resistance. We recently reported an oncogenic role for non-ATPase members of the 19S proteasome in chronic myeloid leukemia (CML), acute myeloid leukemia (AML), and several different solid tumors. In the present study, we hypothesized that ATPase members of the 19S proteasome would also serve as biomarkers and putative therapeutic targets in AML and multiple other cancers. Using data from The Cancer Genome Atlas (TCGA) and the Clinical Proteomic Tumor Analysis Consortium (CPTAC), the expression of proteasome 26S subunit, ATPases 1-6 (PSMC1-6) of the 19S proteasome was elevated in several cancers compared with normal controls, which often correlated with worse overall survival. Altogether, our data suggest that components of the 19S proteasome could serve as prognostic biomarkers and novel therapeutic targets in AML and several other human malignancies.